Determining infrared radiation intensity characteristics for the exhaust manifold of gas turbine engine ТВ3-117 in МІ-8МSB-B helicopter - Kinashchuk, Mykhailo; Kinashchuk, Ihor (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the screen-exhaust device in the TV3-117 engine of the Mi-8MSB-B helicopter. To reduce visibility in the thermal range, a system of mixing hot engine exhaust gases with ambient air is used; this technique makes it possible to reduce the infrared radiation of engines. For this purpose, a new sample of screen-exhaust device was designed for testing. A thermal imaging survey of the helicopter was conducted. Three variants of thermal images were acquired: a helicopter without installation of a thermal visibility reduction system, a helicopter with standard exhaust shields installed, and a helicopter with newly developed shield exhaust devices installed. Based on the obtained experimental results, the characteristics of the intensity of infrared radiation were determined for three variants of research in the range of thermal waves of 3–5 μm. The study uses a comprehensive approach to solving the tasks, which includes a statistical analysis of known and promising ways to protect a helicopter from guided missiles with infrared homing heads based on reduced radiation forces and a theoretical method for calculating flow and temperature fields. The advantages of placing the section of the exhaust channel of the designed screen-exhaust device in the horizontal plane for complete shielding of infrared radiation in the lower hemisphere have been experimentally proven. The benefits of directing the flow of exhaust gases from the screen-exhaust device into the space above the helicopter propeller and dividing this flow into four separate flows were shown. The results of experimental research could be used to design new or improve existing screen-exhaust devices by the developers of military aviation